Collaborative Problem Based Learning and Students’ Anxiety: An Experimental Study in Algebra Learning - Aulia Eka Putri; Yurizka Melia Sari (Journal of Mathematical Pedagogy (JoMP), 2025)
Mathematical skills and ability are indispensable in the 21st century, especially in the development of modern technology. Thus, an understanding of mathematics is necessary to face future challenges. Unfortunately, math is often perceived as a big challenge by students, especially in affective aspects such as math anxiety. This anxiety is known to have a negative impact on students' performance, working memory, and mathematical ability. Therefore, this study aims to determine how much influence Collaborative Problem Based Learning has in reducing math anxiety. Through post-test data, this study uses quantitative, quasi-experimental methodology. The population is class 10 students in a high school in Gresik Regency (N = 320). By purposive sampling, two classes (64 students) studying Two-Variable Inequality System material were selected, which were divided into experimental groups with CPBL treatment and control groups with conventional learning. This research instrument was modified from Sadia Mahmood and Tahira Khatoon's Mathematics Anxiety Development Instrumen (14 items). The results showed that the application of the CPBL learning model did not have a significant effect on reducing student anxiety. This may be due to the short implementation period (two meetings), inconsistent group collaboration, and and a lot of students are hesitant to seek clarification when they are having trouble understanding algebra.